2021
DOI: 10.1111/soc4.12930
|View full text |Cite
|
Sign up to set email alerts
|

A culture of whiteness: How integration failed in cities, suburbs, and small towns

Abstract: As America's neighborhoods have become more racially diverse in the last half century, are these shared spaces fulfilling the "promise of integration"? In this study, I review the literature on desegregation as it occurs in urban, suburban, and rural places, illuminating how a culture of whiteness works in each of these types of places to reproduce racial domination.The literature on multiethnic urban areas demonstrates how a culture of whiteness reframes gentrification as 'revitalization' and nostalgia, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…We used percentage of neighborhood residents identifying as White as a global measure because structural racism has a differential effect on neighborhoods based on the prevalence of White residents . We used 2017 to 2018 one-year ACS estimates of the prevalence of White residents in each residential neighborhood . We reverse coded estimates in our models so that higher-coded estimates (reflecting fewer White residents) reflected greater structural racism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used percentage of neighborhood residents identifying as White as a global measure because structural racism has a differential effect on neighborhoods based on the prevalence of White residents . We used 2017 to 2018 one-year ACS estimates of the prevalence of White residents in each residential neighborhood . We reverse coded estimates in our models so that higher-coded estimates (reflecting fewer White residents) reflected greater structural racism.…”
Section: Methodsmentioning
confidence: 99%
“…[48][49][50][51][52] We used 2017 to 2018 one-year ACS estimates of the prevalence of White residents in each residential neighborhood. 11,12,20,51,[53][54][55] We reverse coded estimates in our models so that higher-coded estimates (reflecting fewer White residents) reflected greater structural racism.…”
Section: Neighborhood Percentage Of White Residentsmentioning
confidence: 99%
“…Previous work has identified various dynamics and challenges around identity (Murray et al 2019) and inclusion (Murray et al 2023). Long-term community members can feel alienated by rapid changes in community culture and identity (Sherman 2018(Sherman , 2021Sherman and Schafft 2022), and new community members, Socially Engaged Art Approaches to CSCW with Young People in… particularly those of a different cultural, racial or ethnic background, can be denied full participation in community life (Meagher 2009;Shucksmith 2012;Patten et al 2015;Balfour et al 2018;Walton 2021). Although much research exists on the experience of migrant children navigating changing personal, familial and community identities and circumstances (Mistry and Wu 2010;Rutland et al 2012;Compton-Lilly et al 2017), we found a lack of information on the experience of young people in rurban communities.…”
Section: The Communitymentioning
confidence: 99%
“…A sudden increase in diversity is a defining rurban sociogeographic characteristic and presents challenges to former rural communities, where a strong sense of community identity can lead to exclusion for those different to the established demographic (Meagher 2009;Thomas et al 2015;Sherman 2018;Murray et al 2019;Walton 2021). New community members bring with them new ways of life that influence and change community identity, and long-term community members find the identity they are so familiar with being challenged and adapted (Murray et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation